Parenting by lying and children’s lying to parents: the moderating role of children’s beliefs - Low, Petrina Hui Xian (2024)
Introduction: How are children socialized about lying? One way is when parents lie to their children for parenting purposes, known as parenting by lying. Children’s perceptions of such lies (i.e., instrumental lies for their compliance, white lies for their benefit) are crucial to how they learn to lie. However, we do not know how children are socialized about lying through their exposure to and belief in different types of parental lies. Aim and Method: We surveyed 564 parent-child dyads from Singapore’s largest birth cohort study (children aged 11 to 12) to collect multi-informant reports on instrumental lies, white lies, belief in parental lies (how true children think the lies are), and children’s lying to parents. We explored the implications of instrumental and white lies on children’s lying, and how children’s belief moderates these relationships. Results: Children's reported exposure to instrumental lies was associated with greater lying to parents (B=0.30, SE=0.04 for child-report; B=0.13, SE=0.03 for parent-report, ps<.001). For white lies, belief in white lies moderated this relationship (B=-0.09, SE=0.04 for child-report; B=0.14, SE=0.03 for parent-report child lying, ps<.01), but simple effects differed by reporter. Exposure to white lies was associated with more child-reported lying to parents only when belief was low (B=0.28, SE=0.06, p<.001), but associated with more parent-reported lying to parents when belief was high (B=0.24, SE=0.06, p<.001). Conclusions: Our findings underscore the importance of children’s perceptions and belief in parental lies in their socialization. We further propose incremental value in differentiating between parental lies and reporters for parenting by lying research.